Measuring and monitoring patient safety in hospitals in Saudi Arabia - Yazeed Kaud (BMC, 2021)
Abstract Background There is much variability in the measurement and monitoring of patient safety across healthcare organizations. With no recognized standardized approach, this study examines how the key components outlined in Vincent et al’s Measuring and Monitoring Safety (MMS) framework can be utilized to critically appraise a healthcare safety surveillance system. The aim of this study is to use the MMS framework to evaluate the Saudi Arabian healthcare safety surveillance system for hospital care. Methods This qualitative study consisted of two distinct phases. The first phase used document analysis to review national-level guidance relevant to measuring and monitoring safety in Saudi Arabia. The second phase consisted of semi-structured interviews with key stakeholders between May and August 2020 via a video conference call and focused on exploring their knowledge of how patient safety is measured and monitored in hospitals. The MMS framework was used to support data analysis. Results Three documents were included for analysis and 21 semi-structured interviews were conducted with key stakeholders working in the Saudi Arabian healthcare system. A total of 39 unique methods of MMS were identified, with one method of MMS addressing two dimensions. Of these MMS methods: 10 (25 %) were concerned with past harm; 14 (35 %) were concerned with the reliability of safety critical processes, 3 (7.5 %) were concerned with sensitivity to operations, 2 (5 %) were concerned with anticipation and preparedness, and 11 (27.5 %) were concerned with integration and learning. Conclusions The document analysis and interviews show an extensive system of MMS is in place in Saudi Arabian hospitals. The assessment of MMS offers a useful framework to help healthcare organizations and researchers to think critically about MMS, and how the data from different methods of MMS can be integrated in individual countries or health systems.